Peran Aparat Kepolisian dalam Mengatasi Pencurian Sepeda Motor: Evaluasi Efektivitas Penegakan Hukum - Maria Clara Elfrisma Manalu; Paiman Nadeak; Ray Dinho Simatupang; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Criminal law consists of regulations. which determines what is prohibited and what is permitted in criminal cases, and determines the punishment that can be given to people who commit them. It is easy to measure the success of Indonesia's legal reform. One of the criminal acts of theft that is often considered to occur very often is motorbike theft. Motorbikes are an important means of transportation for most Indonesian people because the price is affordable for most people with middle to lower incomes, where the increase in the number of motorized vehicles is in line with the increase in the number of crimes involving motorbikes which has led to the crime of motorbike theft. The author uses qualitative legal research with secondary data sources in this research. In this article, the research method used is the normative news method. The Police of the Republic of Indonesia have direct authority to carry out all criminal acts, including theft with violence. This is in accordance with the police's duty to maintain security and public order, protection, protection and community service, as well as law enforcement. In the law enforcement process, efforts are made to uphold functions with legal norms as guidelines for behavior in traffic or legal relations in society and the state where there are perpetrators who commit the criminal act in question, in the sense of people who, with some intention or something unintentional, as required by law, have left a consequence of climbing the law whether it is subjective elements or other elements and in article 362 of the Criminal Code it is explained that the act of taking an item which in whole or in part includes a statement by another person with the intention of possessing the item in violation of the rights.